Membongkar Kinerja Keuangan: Strategi dengan Analisis Common Size di Mandiri Perkasa Interior - Astuti, Fifi; Lukman, Siti Diva Syarifah; Anggerwati, A. Indah; Hasan, Hamida (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This study conducts a financial performance analysis of Mandiri Perkasa Interior utilizing common size analysis as a tool. The findings reveal fluctuations in balance sheet items such as cash, receivables, and inventory. The company demonstrates a tendency to utilize more external funding sources. The analysis also highlights a stable increase in sales and operational expenses, along with efficient tax management. Net profit after tax shows a consistent upward trend during the observed period.